Effective Atom-Atom Potentials for H2O–He and H2O–Ar Systems; Atmospheric and Oceanic Optics; Vol. 31, iss. 2 - Starikov V. I. Vitaly Ivanovich; Petrova T. M. Tatjyana Mikhaylovna; Solodov A. M. Aleksandr Mikhaylovich; Solodov A. A. Aleksandr Aleksandrovich; Deychuli V. M. Vladimir Mikhaylovich (2018, 2018)
Title screen